Pathomorphological analysis of the gum tissues in the application of the combination of Soderm®-Forte gel with Cytoflavin® in experimental periodontitis in rats - Pavel A. Galenko-Yaroshevsky; Aleksandr А. Slavinskiy; Mark A. Zadorozhniy; Valeriy K. Leontev; Artur V. Kheigetyan; Viktor L. Popkov; Anait V. Zelenskaya; Lyudmila M. Chuprinenko; Aleksandr А. Verevkin; Izabella G. Lomsadze; Mariya Yu. Materenchuk; Svetlana A. Lebedeva (Belgorod National Research University, 2023)
Introduction: Periodontitis is one of the most urgent problems of modern dentistry. The development of new paradigms and regimens of combination therapy of patients with periodontitis is a strategic task for pharmacologists and dentists. In view of this, pathomorphological examination is of high importance, since it allow us to conclude about the therapeutic effectiveness of the administered drugs with high objectivity. Aim of the study: to evaluate the effect of the composition of Soderm®-Forte and Cytoflavin® on the pathomorphological pattern of gum tissues of rats with experimental periodontitis (EP). Materials and Methods: EP was simulated in rats by ligature method. Study design: animals with intact periodontium; animals with untreated EP; animals with EP treated with traditional drug therapy (TDT); animals with EP treated with the combination of TDT and Soderm®-Forte gel; and animals with EP treated with the combination of TDT, Soderm®-Forte and Cytoflavin®. For pathomorphological examination, biopsy specimen was taken from the gingival margin of the lower incisors. Slides were stained with hematoxylin and eosin, as well as by Masson. Computer morphometry was performed using the ImageJ software. Results: In EP, TDT has a moderate positive effect on pathomorphological changes in the gum. The combination of TDT and Soderm®-Forte and, to a greater degree, the combination of TDT, Soderm®-Forte and Cytoflavin® have high therapeutic efficacy, characterized by rapid regeneration of the gum tissues. Conclusion: The combination of TDT, Soderm®-Forte and Cytoflavin® in EP has a more pronounced therapeutic effect, manifested by early regression of pathological changes and acceleration of tissue regeneration in the gum.